Mosses from Kakenauwe Natural Reserve and Lambusango Game Reserve, Buton Island, Southeast Sulawesi - FLORENTINA INDAH WINDADRI (Biodiversitas Journal of Biological Diversity, 2007)
Species diversity of Bryophyte in Kakenauwe Natural Reserve and Lambusango Game Reserve has never reported before. Recent floristic study recorded 14 species belong to 12 genus and 8 families occur in this area. Five species of them indicated as a new record for Sulawesi.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: bryophyte, musci, diversity, conservation areas, Buton, South East Sulawesi